نمزجة وحساب احتمالية نشوب الحرائق في المعامل والمنشآت الصناعية - جورج اسبر; هلا مشقوق (Tishreen University, 2019)
International statistics have shown that the number of fire accidents resulting from electric equipment failures and non-functioning of protection systems is enormous. Overheating the coils of electrical motors leads to the possibility of the ignition of  the insulation of electric conductors causing the spread of fire, especially if the frames of these motors contribute more to the spread of fires to the neighboring regions. The most common systems causing the increase of overloading electric motors are the non-symmetry of the input tension to these motors. This gives rise to a negative sequence of currents overlaying a direct sequence of currents leading to an additional increase in heating the rotor, stators, to the wearing and charring of  the insulation of the motors, and finally to fire outbreak. In this research, we aim to estimate and calculate the probability of fire outbreak in electric equipment at industrial plants, checking the reliability embedded within the protection systems, so that the probability of fire occurrence resulting from induction motors is compatible with international standards and criteria.   إن زيادة تسخين وشائع التجهيزات الكهربائية يؤدي إلى احتمال انهيار عازلية الكابلات الكهربائية، وبالتالي اشتعالها وانتشار الحريق وخاصة إذا كانت هياكل هذه التجهيزات مغطاة بطبقات من الغبار والمشبعة بالزيوت, فهي تساهم أكثر في انتشار الحرائق إلى المناطق المجاورة. إن أكثر الأنظمة الشائعة المسببة لزيادة تحميل الآلات الكهربائية هي عدم تناظر توتر الدخل إلى هذه الآلات، وهذا يؤدي إلى ظهور تيارات التتابع العكسي التي تُضاف على تيارات التتابع المباشر, وهذا يقود إلى  زيادة إضافية في تسخين وشائعها, وفي النهاية اهتراء عازليتها وتفحمها ونشوب الحريق. نهدف في هذا البحث إلى تقدير وحساب احتمالية نشوب الحرائق في المنشآت الصناعية التي تستخدم التجهيزات الكهربائية، ومعرفة الوثوقية التي يجب أن تتمتع بها أنظمة الحماية لكي يكون احتمال حدوث الحريق الناتج بسبب هذه التجهيزات مطابقاً للمواصفات القياسية المعيارية العالمية.